Are candidate neurocognitive endophenotypes of OCD present in paediatric patients? A systematic review. (January 2020) - Marzuki, Aleya A.; Pereira de Souza, Ana Maria Frota Lisboa; Sahakian, Barbara J.; Robbins, Trevor W.
Highlights: Action monitoring, decision-making, and planning are affected in child-OCD. Patients show aberrant activation of cortico-fronto-striatal regions. Less evidence for cognitive flexibility, response inhibition, and memory deficits. Abstract: To-date it has been difficult to ascertain the exact cognitive profile of childhood OCD as studies report variable results. Adult OCD research lately utilises the endophenotype approach; studying cognitive traits that are present in both patients and their unaffected first-degree relatives, and are thought to lie closer to the genotype than the full-blown disorder. By observing whether candidate endopenotypes of adult OCD are present in child patients, we can determine whether the two subtypes show cognitive overlap. We conducted a systematic review of the paediatric OCD literature focussing on proposed neurocognitive endophenotypes of OCD: cognitive flexibility, response inhibition, memory, planning, decision-making, action monitoring, and reversal learning. We found that paediatric patients present robust increases in brain error related negativity associated with abnormal action monitoring, impaired decision-making under uncertainty, planning, and visual working memory, but there is less evidence for deficits in other cognitive domains. This implies that children with OCD show some cognitive similarities with adult patients, but other dysfunctions may only manifest later in the disorder trajectory.